Database systems : the complete book - Garcia-Molina, Hector; Ullman, Jeffrey D. , 1942-; Widom, Jennifer (Upper Saddle River, New Jersey : Pearson Prentice Hall, 2009)
For Database Systems and Database Design and Application courses offered at the junior, senior and graduate levels in Computer Science departments. Written by well-known computer scientists, this introduction to database systems offers a comprehensive approach, focusing on database design, database use, and implementation of database applications and database management systems. The first half of the book provides in-depth coverage of databases from the point of view of the database designer, user, and application programmer. It covers the latest database standards SQL:1999, SQL/PSM, SQL/CLI, JDBC, ODL, and XML, with broader coverage of SQL than most other texts. The second half of the book provides in-depth coverage of databases from the point of view of the DBMS implementor. It focuses on storage structures, query processing, and transaction management. The book covers the main techniques in these areas with broader coverage of query optimization than most other texts, along with advanced topics including multidimensional and bitmap indexes, distributed transactions, and information integration techniques
1. Relational database modeling -- 2. Relational database programming -- 3. Modeling and programming for semistructured data -- 4. Database system implementation -- 5. Other issues in management of massive data
Previous edition: 2002
Includes bibliographical references (p. 1179-1181) and index
Keywords: Database design; Database management; Databases